2009
DOI: 10.1111/j.1464-410x.2008.08111.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable braided poly(lactic‐co‐glycolic acid) urethral stent combined with dutasteride in the treatment of acute urinary retention due to benign prostatic enlargement: a pilot study

Abstract: OBJECTIVE To evaluate, in a pilot study, the efficacy and safety of combining a braided poly(lactic‐co‐glycolic acid) (PLGA, a copolymer of l‐lactide and glycolide) urethral stent and dutasteride in the treatment of acute urinary retention (AUR) due to benign prostatic enlargement (BPE). PATIENTS AND METHODS Ten men with AUR due to BPE were treated as outpatients. A biodegradable braided PLGA urethral stent was inserted into the prostatic urethra, using a specially designed insertion device under visual contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…55 Use of a bio-absorbable braided urethral stents is also being piloted in regard to its efficacy and safety and has yielded promising results when combined with dutasteride (LE: IV). 56 All subjects (n = 10) were able to void short term and 50% of subjects were still able to spontaneously void at 3 months. 56 …”
Section: Surgical Interventionmentioning
confidence: 92%
See 1 more Smart Citation
“…55 Use of a bio-absorbable braided urethral stents is also being piloted in regard to its efficacy and safety and has yielded promising results when combined with dutasteride (LE: IV). 56 All subjects (n = 10) were able to void short term and 50% of subjects were still able to spontaneously void at 3 months. 56 …”
Section: Surgical Interventionmentioning
confidence: 92%
“…56 All subjects (n = 10) were able to void short term and 50% of subjects were still able to spontaneously void at 3 months. 56 …”
Section: Surgical Interventionmentioning
confidence: 98%
“…A biodegradable braided poly(lactic-co-glycolic acid) (PLGA) prostatic stent has been used in combination with dutasteride for the management of acute urinary retention. 24 Ten such patients were able to void after the stent insertion, and half of them continued to be able to do so after 3 months. None of the patients had any migration of the stent or incontinence due to the stent.…”
Section: Biodegradable Stentsmentioning
confidence: 94%
“…This novel braided PLGA stent seems to overcome the earlier problems of migration and breakage into large particles. 24 Nevertheless, the mechanical properties of the stent need to be improved and tested in a longer follow-up.…”
Section: Biodegradable Stentsmentioning
confidence: 99%
“…They found that the stents were easy to insert and they degraded smoothly over a period of 1–2 months. This stent design was then used in a pilot study along with dutasteride in the treatment of acute urinary retention due to BPH 19. Ten men with acute urinary retention due to BPH were treated in an outpatient setting.…”
Section: Temporary Stentsmentioning
confidence: 99%